Magyar népesség, magyar identitás az Őrvidéken Ausztriában, egy kérdőíves felmérés tapasztalatai = Hungarian minority, Hungarian identity in Burgenland, Austria, experience a questionnaire survey - Hegedűsné Baranyai, Nóra; Bali, Lóránt; Szabó, Péter (Közép-Európai Közlemények, 2017)
Under Lakitelek Aduit Education College we took part in a field research in Burgenland úvo times fór a week. We managed to find indigenous Hungárián inclusions. These are the last episodes of Hungárián-Austrian community. Their cultural and education system is developped, even though the community is towards its annihilation. Within the framework of the questionnaire survey, we processed the answers given fór the questions related to population, education, minority life and language. The overall picture of the research will be evaluated with the help of a SWOT-analysis.